A test method for quickly judging the slagging property of coal ash
After the coal ash sample is treated, dry, and crushed, the pH value is evenly scattered in the water, which solves the problem of judging coal ash for a long time in the existing technology, and achieved rapid and effective slag. Judgment, suitable for the actual operating environment.
Patent Information
- Application Number
- CN202111156368.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-29
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-09-29
AI Technical Summary
In the prior art, it takes 7 days to judge the slag properties of coal ash, and the result is lagging, which cannot meet the needs of rapid judgment.
After the raw coal sample is treated, dry, and broken through the pile cone, it is evenly scattered in the water after removing the carbon dioxide, and the pH value of the liquid to be measured is determined to determine the slag of the coal ash.
This method has significantly shortened coal ash slag detection cycles, can obtain judgment results within a few hours, improves judgment efficiency, suitable for the actual operating environment, and ensure the safe operation of boilers and energy conservation.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of coal chemical testing and relates to a test method for quickly judging the slagging property of coal ash. Background Art
[0002] During the combustion process of pulverized coal boiler, slagging is the molten slag generated by the collision of softened or molten ash particles on the water-cooled wall and the main radiation heating surface. Its surface is often piled with a harder slag sintering layer. Accurate and rapid judgment of the slagging performance of coal ash is crucial to the safe and economical operation of the unit. So far, numerous judgment methods and criteria have been established in this regard. The basic test method now adopts "GB / T1574-2007 Coal Ash Composition Analysis Method" and "DL / T1037-2007 Coal Ash Composition Analysis Method" to prepare the coal sample into a general analysis test coal sample, then weigh a certain amount of coal sample, and after burning it at 815℃ in a resistance furnace for 3-4 hours, prepare the prepared ash sample into a test solution, and then use the chemical method of artificial titration to separate the acidic oxides SiO2, The results of Fe2O3, Al2O3, TiO2, SO3, and P2O3 are calculated, and then the contents of basic oxides CaO, MgO, K2O, Na2O, and MnO2 are determined by atomic spectrophotometer or atomic emission spectrometry. The slagging properties of the coal ash are judged by the ratio of acidic oxides to basic oxides in the coal ash. It takes 7 days from the preparation of an ash sample to the submission of test results. The analysis results often take a long time and the judgment results are delayed. Summary of the invention
[0003] In order to overcome the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a test method for quickly judging the slagging properties of coal ash, thereby improving the efficiency of judging the slagging properties of coal ash and meeting the working condition requirement of obtaining the test results in a timely manner.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions:
[0005] A test method for quickly judging the slagging property of coal ash comprises the following steps:
[0006] The raw coal samples are mixed evenly and then subjected to an inverted cone treatment to obtain a reduced coal sample; the reduced coal sample is dried and then cooled to room temperature to obtain a dry coal sample; the moisture content of the dry coal sample is measured, and the coal sample after the moisture content is measured is crushed and then sieved to obtain a coal sample powder;
[0007] The obtained coal sample powder is evenly dispersed in water after the carbon dioxide is removed to obtain a mixed system, the obtained mixed system is allowed to stand for sedimentation, and the filtrate is collected by filtration to obtain a test solution; and the pH value of the obtained test solution is determined;
[0008] The slagging properties of the coal ash are determined based on the pH value of the test liquid: when the pH value is between 9.00 and 12.00, the result is determined to be slagging coal.
[0009] A further improvement of the present invention is:
[0010] Preferably, when the pH value is 1.00 to 4.00, the judgment result is no slagging;
[0011] When the pH value is 4.00-8.00, the result is judged as slight slagging.
[0012] Preferably, the inverted cone treatment is performed no less than 3 times.
[0013] Preferably, the obtained shrunken coal sample is dried in an inert atmosphere or an air atmosphere.
[0014] Preferably, the drying temperature of the obtained shrunken coal sample is 105°C to 110°C.
[0015] Preferably, the dried shrunken coal sample is cooled to room temperature, and the specific operation includes:
[0016] After the dried shrunken coal sample is placed in the air for 5 to 10 minutes, it is placed in a dryer and cooled to room temperature.
[0017] Preferably, the coal sample after the moisture content is measured is crushed and then sieved, and the specific operation includes:
[0018] The coal samples after moisture determination were crushed to 1-1.25 mm and sieved through a standard test sieve.
[0019] Preferably, the mixing ratio of the obtained coal sample powder and water is 4.99-5.01 g: 200 mL;
[0020] The mixing temperature of the obtained coal sample powder and water is 25±3°C.
[0021] Preferably, the pH value is detected at a temperature of 25±3°C.
[0022] Preferably, the pH value of the obtained test solution is determined, and the specific steps include:
[0023] The water after the removal of carbon dioxide is used as a blank test; the water used in the blank test and the mixed system are subjected to a dispersion stirring treatment and a static sedimentation treatment of the mixed system at the same time;
[0024] Use an acidity meter to measure the pH values of the test solution and the blank test, and record them separately after the pH values stabilize.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention discloses a test method for quickly judging the slagging property of coal ash. By obtaining the reduced coal sample, the utilization rate of the original coal sample can be improved and the sample quantity requirement can be reduced. By evenly dispersing the coal sample powder in water, the detection object of the soluble ions in the prior art can be converted into the influence of the ion hydrolysis on the pH value of the system, thus avoiding the tedious operation of ion titration. Therefore, the method for quickly judging the slagging property of coal ash described in the present invention can effectively shorten the detection cycle of the slagging property of coal ash and improve the judgment efficiency of the slagging property of coal ash. At the same time, the judgment method described in the present invention has simple process steps and can be applied to the actual working environment of the industry. It is of great significance to reduce or inhibit the deposition of coal ash for the blending of coal for boilers, ensure the safe operation of boilers, reduce costs, save energy, improve thermal efficiency and economic benefits, and protect the environment.
[0027] In summary, the method for quickly judging the slagging property of coal ash of the present invention has the following advantages:
[0028] (1) The present invention provides a method for quickly determining the slagging property of coal ash. The obtained results can accurately determine the slagging property of the coal entering the plant and the coal entering the furnace of a coal-fired power plant, so as to provide data support for the blending of coal in the boiler to reduce or inhibit the deposition of coal ash, ensure the safe operation of filtration, reduce costs, save energy, and improve thermal efficiency and economic benefits;
[0029] (2) The method for quickly judging the slagging properties of coal ash provided by the present invention greatly shortens the detection time. The judgment result can be obtained in just a few hours. Compared with the 7-day detection time in the prior art, the present invention can achieve the purpose of rapid judgment. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0031] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those described herein. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0032] The present invention is further described in detail below in conjunction with specific embodiments:
[0033] Example 1
[0034] This embodiment provides a test method for quickly judging the slagging property of coal ash. The raw coal sample of Yinxing No. 1 Mine is selected for judgment. The method is specifically performed in the following steps:
[0035] Step 1: According to the "GB475-2008 Commercial Coal Sampling Method", 3.75 kg of raw coal sample with a nominal particle size of 6 mm is taken, mixed evenly, and stacked three times with an inverted cone, and 1.25 kg of the shrunken coal sample is put into a sample barrel and sealed for storage;
[0036] Step 2: Weigh 10 g of the reduced coal sample and place it in a glass weighing bottle with a diameter of 70 mm and a height of 40 mm and a tightly sealed lid. Open the lid and place it in a nitrogen-filled drying oven preheated to 110°C and dry it for 3 hours. After drying, take out the dried coal sample, place it in the air for 5 minutes, place it in a dryer to cool the coal sample to room temperature, weigh it, and calculate the moisture content of the coal sample. The moisture content of the coal sample is calculated according to formula (1).
[0037]
[0038] Where M t is the moisture content of the coal sample (%), m1 is the mass loss of the coal sample after drying, in g, and m is the weighed mass of the reduced coal sample, in g.
[0039] Step 3, the coal sample after the moisture content is determined is further crushed to 1 mm, and sieved with a 1 mm standard test sieve with a pass rate of 95%, thereby obtaining the coal sample powder under the sieve;
[0040] Step 4. At room temperature, place 5 g of the sieve-under coal sample powder in a 250 ml plastic beaker, carefully add 200 ml of ultrapure water from which carbon dioxide has been removed, place the plastic beaker containing the sieve-under coal sample solution on a magnetic stirrer, add a stirrer, cover with a watch glass, control the temperature of the sieve-under coal sample solution to 25°C, stir at 400 r / min for 1 hour, let stand and settle for 10 minutes, filter with dry medium-speed quantitative filter paper without washing, collect the filtrate in a 200 ml plastic volumetric flask, seal and store for later use;
[0041] Step 5. Use a pipette to measure 50 ml of the filtrate and put it in a plastic beaker. Use an acidometer to determine the pH value of the filtrate. First, the acidometer is installed and debugged normally, and a calibrated acidometer electrode is used for measurement. The filtrate temperature is controlled to 25°C and stirred for 3 minutes. After the data is stable, the pH value is recorded to obtain the test results (referred to as the present invention). The results are shown in Table 1.
[0042] Example 2
[0043] The method is the same as that in Example 1, except that the raw coal sample of Shigouyi Mine is selected for judgment in this embodiment, and the inverted cone treatment is performed 5 times; the obtained shrunken coal sample is dried in an air drying oven at a drying temperature of 105°C; the dried shrunken coal sample is placed in the air for 10 minutes, and then placed in a dryer to cool to room temperature; the coal sample after the moisture content is measured is crushed to 1.25 mm and sieved through a standard test sieve, and the pass rate is 96%; the mixing ratio of the obtained coal sample powder and water is 5.01 g: 200 mL, and the mixing temperature is 28°C; the filtrate temperature is controlled to 28°C and stirred for 3 minutes, and the pH value is recorded after the data is stable to obtain the pH value of the liquid to be tested. The results are shown in Table 1.
[0044] Example 3
[0045] The method is the same as that in Example 1, except that the raw coal sample of Yanger Mine is selected for judgment in this embodiment, and the inverted cone treatment is performed 4 times; the obtained shrunken coal sample is dried in an air drying oven at a drying temperature of 107°C; the dried shrunken coal sample is placed in the air for 8 minutes, and then placed in a dryer to cool to room temperature; the coal sample after the moisture content is measured is crushed to 1.1 mm and sieved through a standard test sieve, and the pass rate is 98%; the mixing ratio of the obtained coal sample powder and water is 4.99g:200mL, and the mixing temperature is 22°C; the filtrate temperature is controlled to 22°C and stirred for 3 minutes, and the pH value is recorded after the data is stable to obtain the pH value of the liquid to be tested. The results are shown in Table 1.
[0046] Example 4
[0047] The method is the same as that in Example 1, except that the raw coal sample of Lingxin Mine is selected for judgment in this embodiment, and the inverted cone treatment is performed 6 times; the obtained shrunken coal sample is dried in an air drying oven at a drying temperature of 109°C; the dried shrunken coal sample is placed in the air for 7 minutes, and then placed in a dryer to cool to room temperature; the coal sample after the moisture content is measured is crushed to 1.2 mm and sieved through a standard test sieve, and the pass rate is 95%; the mixing ratio of the obtained coal sample powder and water is 4.99 g: 200 mL, and the mixing temperature is 23°C; the filtrate temperature is controlled to 26°C and stirred for 3 minutes, and the pH value is recorded after the data is stable to obtain the pH value of the liquid to be tested. The results are shown in Table 1.
[0048] Example 5
[0049] The method is the same as that in Example 1, except that the raw coal sample of Meihuajing Mine is selected for judgment in this embodiment, and the inverted cone treatment is performed 4 times; the obtained shrunken coal sample is dried in an air drying oven at a drying temperature of 108°C; the dried shrunken coal sample is placed in the air for 6 minutes, and then placed in a dryer to cool to room temperature; the coal sample after the moisture content is measured is crushed to 1mm and sieved through a standard test sieve, and the pass rate is 95%; the mixing ratio of the obtained coal sample powder and water is 5.01g:200mL, and the mixing temperature is 27°C; the filtrate temperature is controlled to 22°C and stirred for 3 minutes, and the pH value is recorded after the data is stable to obtain the pH value of the liquid to be tested. The results are shown in Table 1.
[0050] Example 6
[0051] The method is the same as that in Example 1, except that the raw coal sample from Shicao Village Mine is selected for judgment in this example. The results are shown in Table 1.
[0052] Example 7
[0053] The method is the same as that in Example 1, except that the raw coal sample of Zaoquan Mine is selected for judgment in this example. The results are shown in Table 1.
[0054] Example 8
[0055] The method is the same as that in Example 1, except that the raw coal sample from Yangyi Mine is selected for judgment in this example. The results are shown in Table 1.
[0056] Example 9
[0057] The method is the same as that in Example 1, except that the raw coal sample of Hongliu Mine is selected for judgment in this example. The results are shown in Table 1.
[0058] Example 10
[0059] The method is the same as that in Example 1, except that the raw coal sample of Jinfeng Mine is selected for judgment in this example. The results are shown in Table 1.
[0060] Embodiment 11
[0061] The method is the same as that in Example 1, except that the raw coal sample of Shuangma Mine is selected for judgment in this example. The results are shown in Table 1.
[0062] Example 12
[0063] The method is the same as that in Example 1, except that the raw coal sample of Ningdian raw coal is selected for judgment in this example. The results are shown in Table 1.
[0064] Embodiment 13
[0065] The method is the same as that in Example 1, except that the raw coal sample of Ningdian high calorific raw coal is selected for judgment in this example. The results are shown in Table 1.
[0066] Embodiment 14
[0067] The method is the same as that in Example 1, except that the raw coal sample of Ningdian low-calorific raw coal is selected for judgment in this example. The results are shown in Table 1.
[0068] Embodiment 15
[0069] The method is the same as that in Example 1, except that the raw coal sample of Ningdian mixed coal is selected for judgment in this example. The results are shown in Table 1.
[0070] Example 16
[0071] The method is the same as that in Example 1, except that the raw coal sample of the gangue of Yinxing Mine is selected for judgment in this example. The results are shown in Table 1.
[0072] Embodiment 17
[0073] The method is the same as that in Example 1, except that the raw coal sample from Lingwu Mine is selected for judgment in this example. The results are shown in Table 1.
[0074] Embodiment 18
[0075] This embodiment provides a test method for quickly judging the slagging property of coal ash. The raw coal sample of Yinxing No. 1 Mine is selected for judgment. The method is specifically performed in the following steps:
[0076] Step 1: According to GB475-2008 Commercial Coal Sampling Method, 3.75 kg of raw coal sample with a nominal particle size of 6 mm is taken, mixed evenly, and stacked upside down for 4 times. 1.25 kg of coal sample is separated and placed in a sample barrel for sealing and storage for later use;
[0077] Step 2: Weigh 9.99 g of coal sample and put it into a glass weighing bottle with a diameter of 70 mm and a height of 40 mm and a tight sealing lid. Open the lid and put it into a nitrogen-filled drying oven preheated to 105°C for 4 hours. After drying, take out the coal sample, place it in the air for 5 minutes, put it in a dryer to cool the coal sample to room temperature, and weigh it.
[0078]
[0079] Where M t is the moisture content of the coal sample (%), m1 is the mass loss of the coal sample after drying, in g, and m is the weighed mass of the coal sample, in g.
[0080] Step 3, the coal sample after the moisture content is determined is further crushed to 1 mm, and sieved with a 1 mm standard test sieve with a pass rate of 95%, thereby obtaining a coal sample under the sieve;
[0081] Step 4, at room temperature, place 4.99g of the sieve-under coal sample in a 250ml plastic beaker, carefully add 200ml of ultrapure water from which carbon dioxide has been removed, place the plastic beaker containing the sieve-under coal sample solution on a magnetic stirrer, add a stirrer, cover with a watch glass, control the temperature of the sieve-under coal sample solution to 22°C, stir at 300r / min for 2h, let stand and settle for 10min, filter with dry medium-speed quantitative filter paper without washing, collect the filtrate in a 200ml plastic volumetric flask, seal and store for later use;
[0082] Step 5. Use a pipette to measure 50 ml of the filtrate and put it in a plastic beaker. Use an acidometer to determine the pH value of the filtrate. First, install and debug the acidometer normally, measure with a calibrated acidometer electrode, control the filtrate temperature to 22°C, stir for 3 minutes, and record the pH value after the data stabilizes. The slagging properties of the coal ash are judged by the pH value.
[0083] Embodiment 19
[0084] This embodiment provides a test method for quickly judging the slagging property of coal ash, and selects the raw coal sample of Shigouyi Mine for judgment, and specifically follows the following steps:
[0085] Step 1: According to GB475-2008 Commercial Coal Sampling Method, 3.75 kg of raw coal sample with a nominal particle size of 6 mm is taken, mixed evenly, and stacked three times with an inverted cone. 1.25 kg of coal sample is separated and placed in a sample barrel, sealed and stored for later use;
[0086] Step 2: Weigh 10.01 g of coal sample and put it into a glass weighing bottle with a diameter of 70 mm, a height of 40 mm and a tightly sealed lid. Open the lid and put it into a nitrogen-filled drying oven preheated to 107°C for 3.5 hours. After drying, take out the coal sample, place it in the air for 5 minutes, put it in a dryer to cool the coal sample to room temperature, weigh it, and calculate the moisture content of the coal sample. The moisture content of the coal sample is calculated according to formula (1).
[0087]
[0088] Where M t is the moisture content of the coal sample (%), m1 is the mass loss of the coal sample after drying, in g, and m is the weighed mass of the coal sample, in g.
[0089] Step 3, the coal sample after the moisture content is determined is further crushed to 1.25 mm, and sieved with a 1.25 mm standard test sieve with a pass rate of 98%, thereby obtaining a coal sample under the sieve;
[0090] Step 4. At room temperature, place 5.01 g of the sieve-undersized coal sample in a 250 ml plastic beaker, carefully add 200 ml of ultrapure water from which carbon dioxide has been removed, place the plastic beaker containing the sieve-undersized coal sample solution on a magnetic stirrer, add a stirrer, cover with a watch glass, control the temperature of the sieve-undersized coal sample solution to 28°C, stir at 350 r / min for 1.5 h, let stand and settle for 12 min, filter with dry medium-speed quantitative filter paper without washing, collect the filtrate in a 200 ml plastic volumetric flask, seal and store for later use;
[0091] Step 5. Use a pipette to measure 50 ml of the filtrate and place it in a plastic beaker. Use an acidometer to determine the pH value of the filtrate. First, install and debug the acidometer normally, measure with a calibrated acidometer electrode, control the filtrate temperature to 28°C, stir for 3 minutes, and record the pH value after the data stabilizes.
[0092] In addition, raw coal samples from 17 types of mines in Examples 1-17 were tested according to national standards, and the test results were recorded (referred to as national standard methods). The results are shown in Table 1.
[0093] Table 1 Test samples and result records of Examples 1-17
[0094]
[0095] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A test method for quickly judging the slagging property of coal ash, characterized in that: The following steps are involved: The raw coal samples are mixed evenly and then subjected to an inverted cone treatment to obtain a reduced coal sample; the reduced coal sample is dried and then cooled to room temperature to obtain a dry coal sample; the moisture content of the dry coal sample is measured, and the coal sample after the moisture content is measured is crushed and then sieved to obtain a coal sample powder; The obtained coal sample powder is evenly dispersed in water after the carbon dioxide is removed to obtain a mixed system, the obtained mixed system is allowed to stand for sedimentation, and the filtrate is collected by filtration to obtain a test solution; and the pH value of the obtained test solution is determined; The slagging property of the coal ash is determined according to the pH value of the test liquid: when the pH value is between 9.00 and 12.00, the result is determined to be slagging coal; When the pH value is 1.00-4.00, the judgment result is no slagging; When the pH value is 4.00-8.00, the result is judged as slight slagging; The mixing ratio of the obtained coal sample powder and water is 4.99-5.01 g: 200 mL; The mixing temperature of the obtained coal sample powder and water is 25±3°C; The pH value is tested at 25 ± 3 °C; Determine the pH value of the obtained test solution, the specific steps of which include: The water after the removal of carbon dioxide is used as a blank test; the water used in the blank test and the mixed system are subjected to a dispersion stirring treatment and a static sedimentation treatment of the mixed system at the same time; Use an acidity meter to measure the pH values of the test solution and the blank test, and record them separately after the pH values stabilize.
2. A test method for quickly judging the slagging property of coal ash according to claim 1, characterized in that: The number of inverted cone treatments shall be no less than 3 times.
3. A test method for quickly judging the slagging property of coal ash according to claim 1, characterized in that: The obtained reduced coal sample is dried in an inert atmosphere or an air atmosphere.
4. A test method for quickly judging the slagging property of coal ash according to claim 1, characterized in that: The drying temperature of the obtained reduced coal sample is 105℃~110℃.
5. A test method for quickly judging the slagging property of coal ash according to claim 1, characterized in that: The dried and shrunken coal sample is cooled to room temperature. The specific operation includes: After the dried shrunken coal sample is placed in the air for 5 to 10 minutes, it is placed in a dryer and cooled to room temperature.
6. A test method for quickly judging the slagging property of coal ash according to claim 1, characterized in that: The coal sample after moisture determination is crushed and then sieved. The specific operations include: The coal samples after moisture determination were crushed to 1-1.25 mm and sieved through a standard test sieve.
Citation Information
Patent Citations
High-uniformity quantitative splitting and subpackaging technology of standard coal sample
CN103234798A